The relationship between muscle activation and shear elastic modulus of the sternocleidomastoid muscle during 3-D torque production - Wolff, W. L.; Leonardis, J. M.; Lipps, D. B. (Journal of Electromyography and Kinesiology, 2020)
The sternocleidomastoid (SCM) is a primary neck torque generator, but the relationship between its muscle activation and shear elastic modulus during 3-D torque production is unknown. This study examined variations in neural control and shear elastic modulus of the SCM across various 3-D isometric torques. Our primary hypothesis was that the SCM would display similar preferred directions where muscle activity and shear elastic modulus were maximal during voluntary 3-D isometric torque production. Surface electromyography (EMG) and ultrasound shear wave elastography (SWE) data were collected from the SCM in 20 participants performing 3-D isometric target-matching at two different torque amplitudes. We used spherical statistics to compare the preferred directions calculated from the SWE and EMG data at 40% and 80% torque level during 3-D isometric torque production. We demonstrated a small but significant difference between EMG and SWE preferred directions, with the SWE preferred direction oriented more towards ipsilateral bending and less towards contralateral axial rotation than the preferred direction for the EMG data. We conclude that, although small differences exist, SCM shear elastic modulus is largely driven by activation during 3-D neck torques for healthy individuals.